The mapping of spatial distribution of selected hemipteran (phyyhocoridae and coreidae) at Universiti Teknologi MARA Pahang / Muzamil Mustaffa and Sarina Hashim - Mustaffa, Muzamil; Hashim, Sarina (Universiti Teknologi MARA Cawangan Pahang, 2006)
This paper discusses the mapping of spatial distribution of Dysdercus spp. (Phyyhocoridae) and Anoplocnemis spp. (Coreidae) at Universiti Teknologi MARA (UiTM) Pahang, Jengka Campus plantation area by using Global Positioning System (GPS) and Geographical Information System (GIS). The main objectives are to collect and create a database of insect pest, to determine spatial distribution and predict behavioural pattern of the species above. The sampling was done every 2 days for a period of 30 days. The work was carried out by three men-day. The sampling technique used was by using the insect sweeping net and through direct observation. The coordinate system in terms of longitude and latitude (WGS 84) were recorded by using Garmin eTrex Summit (GPS receiver) for each Dysdercus spp. and Anoplocnemis spp. discovered. At total of 9I individuals of Anoplocnemis spp. and 6 individuals of Dysdercus spp. were recorded during the field study. The data were then associated with the GIS application in order to map the spatial distribution of the insect pests. In conclusion, the combination of database, GPS and GIS provides an excellent tool for predicting and monitoring the behavioural patterns of insect pests especially in a large area.